2014
DOI: 10.2337/db13-1221
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of Sp1 Binding Site Suppresses Hypothalamic POMC in Neonates and May Contribute to Metabolic Disorders in Adults: Impact of Maternal Dietary CLAs

Abstract: Epigenetic regulation of neuropeptide genes associated with central appetite control plays an important part in the development of nutritional programming. While proopiomelanocortin (POMC) is critical in appetite control, the molecular mechanism of methylation-related regulation of POMC remains unclear. Based on the report that the proximal specificity protein 1 (Sp1) binding site in POMC promoter is crucial for the leptin-mediated activation of POMC, the methylation of this site was investigated in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
(41 reference statements)
5
30
0
Order By: Relevance
“…During pregnancy, hormonal shifts occur to support a leptin-resistant state, which is further amplified by consumption of an HF diet [52]. Similarly, lactation is a leptin-resistant state [53], and maternal CLA supplementation during lactation has been shown to increase leptin concentrations, as seen in a pregnant state in the present study [54]. Catalano et al demonstrated that, in obese mothers with elevated leptin, fetuses developed in utero insulin resistance, were heavier at birth and had elevated cord leptin compared to those from lean mothers [55].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…During pregnancy, hormonal shifts occur to support a leptin-resistant state, which is further amplified by consumption of an HF diet [52]. Similarly, lactation is a leptin-resistant state [53], and maternal CLA supplementation during lactation has been shown to increase leptin concentrations, as seen in a pregnant state in the present study [54]. Catalano et al demonstrated that, in obese mothers with elevated leptin, fetuses developed in utero insulin resistance, were heavier at birth and had elevated cord leptin compared to those from lean mothers [55].…”
Section: Discussionmentioning
confidence: 64%
“…Zhang et al demonstrated that maternal CLA administration during lactation may mediate hypermethylation-induced programming in offspring, representing a potential programming mechanism of CLA [54]. Previous studies have reported that maternal CLA during gestation and lactation can have growth and development promoting effects in offspring [57], but findings remain inconsistent [58] and appear to be dependent on offspring sex and the dose/duration of exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Also, we cannot rule out other possible causes of disparities in cell culture and animal studies, such as uncontrolled exposure to other potentially confounding environmental stimuli. For example, epigenetic states at proopiomelanocortin are affected by diet, alcohol, POPs and even early life stress [65, 70, 168170]. Ibrahim and colleagues [180] showed that POP exposure in mice fed contaminated whale meat did not lead to weight gain nor standard metabolic disruption in insulin signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the strong correlation between DNA methylation at proopiomelanocortin, gene expression and phenotypic variation, mechanisms of epigenetic regulation of proopiomelanocortin expression remain unclear. Most recently a study by Zhang and colleagues [65] use cultured cells to show that hypermethylation at the proopiomelanocortin promoter and within the binding site [66] for proximal specificity protein 1 (SP1), blocked formation of the SP1-promoter complex required for activation of proopiomelanocortin. Interestingly, they also showed using a lactation-staged mouse model this aberrant methylation at the proopiomelanocortin promoter is induced by maternal dietary supplementation of conjugated linoleic acids (CLAs).…”
Section: 1 Molecular Pathways Of Obesity Regulated By Nutritionmentioning
confidence: 99%
“…It has been suggested that this phenomenon is at least partially mediated by epigenetic malprogramming of hypothalamic anorexigenic neuropeptides, such as proopiomelanocortin (POMC) (1)(2)(3).…”
mentioning
confidence: 99%